Dakwah Islam dalam Pemikiran lsma'il Raji al-Faruqi - Nasrudin, Nasrudin (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2008)
In the some way as Christianity, Islam poses itself as a preaching religion. A preach for the truth of Islam represents Allah's order and is valued as a  holy preach. The preach to obey God con be seen from different points. Seen from its mod'u, it is offered to oil human beings, regardless their races and languages.  Seen from its materials, Islamic preach covers oil aspects of human life in which universal human values become its principles. According to lsmo'il Roii ol-Foruqi, Islamic preach hos to represents the spirit of freedom, rationality, and universality. Consequently, Islam must be preached in politeness, freedom, and responsibility  as well as without any pressure because the truth of Islam is rational.